Measuring The Level of MIR-148A in Iraqi Women Diagnosed with Breast Cancer - Muna Shukri Mahmood Al-Mashhadani, Wafaa Sabri Mahood, Hazima Mossa Al-Abassi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast cancer is the most common type of cancer in Iraq, and the incidence of it has increased among Iraqi women in the past two decades, as it represents one of the most important threats to women's health. Aim: this study aimed to investigate the miR-148a gene expression as a biomarker in different age groups of Iraqi women with breast cancer, as well as its association with patient characteristics such as body mass index, disease stage, and tumor location. Method: Fifty women diagnosed with breast cancer were enrolled in this study in addition to 25 healthy individuals as a control group. The fold expression (FE) of miRNA-148a was detected by quantitative polymerase chain reaction (qPCR) techniques. Results: The results showed the highest significant difference in the gene expression of miR-148a in breast cancer patients in the age group (50) compared to the control group, and the difference was significant in the age group (<40) compared to the control group, highly significant differences was found in the age group (40-49) compared with the control group. The results also showed no significant differences in the fold level of gene expression for miR-148a in the grades (I, II, and III) of breast cancer patients, and that the highest level was recorded in the second grade, and the highest level was recorded in the grade. Keywords: Breast Cancer, miR-148a, BMI